Aortic aneurysm and craniosynostosis in a family with Cantu syndrome. Issue 1 (25th November 2013) - Hiraki, Yoko; Miyatake, Satoko; Hayashidani, Michiko; Nishimura, Yutaka; Matsuura, Hiroo; Kamada, Masahiro; Kawagoe, Takuji; Yunoki, Keiji; Okamoto, Nobuhiko; Yofune, Hiroko; Nakashima, Mitsuko; Tsurusaki, Yoshinori; et al.
Abstract Cantu syndrome is an autosomal dominant overgrowth syndrome associated with facial dysmorphism, congenital hypertrichosis, and cardiomegaly. Some affected individuals show bone undermodeling of variable severity. Recent investigations revealed that the disorder is caused by a mutation in ABCC9, encoding a regulatory SUR2 subunit of an ATP‐sensitive potassium channel mainly expressed in cardiac and skeletal muscle as well as vascular smooth muscle. We report here on a Japanese family with this syndrome. An affected boy and his father had a novel missense mutation in ABCC9. Each patient had a coarse face and hypertrichosis. However, cardiomegaly was seen only in the boy, and macrosomia only in the father. Skeletal changes were not evident in either patient. Craniosynostosis in the boy and the development of aortic aneurysm in the father are previously undescribed associations with Cantu syndrome. © 2013 Wiley Periodicals, Inc.